ANALISIS BAKTERI SALMONELLA-SHIGELLA PADA KUAH SATE PEDAGANG KAKI LIMA - Rahmiati rahmiati (Universitas Medan Area, 2017)
A study of Analysis Salmonella-Shigella in Sate Sauce, was conducted in Biology Laboratory, Faculty of Biology University Medan Area. The purpose of this study was to find out the bacteria found in the street vendors sate and detect the presence of Salmonella-Shigella in the sample. The results showed that the total number of total bacteria in sample was 24 x 104 CFU. Detection of Salmonelle-Shigella was done by growing bacteria on selective medium of Salmonella Shigella Agar (SSA) and showed positive results for Salmonella bacteria presence by the change of media color from green to blue.